Selective interactions of boundaries with upstream region of Abd-B promoter in Drosophila bithorax complex and role of dCTCF in this process - Kyrchanova, Olga (Oxford University Press, 2011)
Expression of the genes Ubx, abd-A, and Abd-B of the bithorax complex depends on its cis-regulatory region, which is divided into discrete functional domains (iab). Boundary/insulator elements, named Mcp, Fab-6, Fab-7 and Fab-8 (PTS/F8), have been identified at the borders of the iab domains. Recently, binding sites for a Drosophila homolog of the vertebrate insulator protein CTCF have been identified in Mcp, Fab-6 and Fab-8 and also in several regions that correspond to predicted boundaries, Fab-3 and Fab-4 in particular. Taking into account the inability of the yeast GAL4 activator to stimulate the white promoter when the activator and the promoter are separated by a 5-kb yellow gene, we have tested functional interactions between the boundaries. The results show that all dCTCF-containing boundaries interact with each other. However, inactivation of dCTCF binding sites in Mcp, Fab-6 and PTS/F8 only partially reduces their ability to interact, suggesting the presence of additional protein(s) supporting distant interactions between the boundaries. Interestingly, only Fab-6, Fab-7 (which contains no dCTCF binding sites) and PTS/F8 interact with the upstream region of the Abd-B promoter. Thus, the boundaries might be involved in supporting the specific interactions between iab enhancers and promoters of the bithorax complex.